Reading "Invisible" Dead Sea Scrolls - Chapman, Christy (The Biblical archaeology review, 2022)
Technology in the hands of scholars, conservators, and archaeologists alike has long been central to the successful preservation and analysis of the Dead Sea Scrolls. While early technologies involved sticky tape for rejoining fragments and analog photography for their documentation, the advanced tools of today allow fragile scrolls to be read without even unwrapping […]